The Complex Roles and Therapeutic Implications of m6A Modifications in Breast Cancer - Wei, Min; Bai, Jing-Wen; Niu, Lei; Zhang, Yong-Qu; Chen, Hong-Yu; Zhang, Guo-Jun (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidence indicates that N6-methyladenosine (m6A), which directly regulates mRNA, is closely related to multiple biological processes and the progression of different malignancies, including breast cancer (BC). Studies of the aberrant expression of m6A mediators in BC revealed that they were associated with different BC subtypes and functions, such as proliferation, apoptosis, stemness, the cell cycle, migration, and metastasis, through several factors and signaling pathways, such as Bcl-2 and the PI3K/Akt pathway, among others. Several regulators that target m6A have been shown to have anticancer effects. Fat mass and obesity-associated protein (FTO) was identified as the first m6A demethylase, and a series of inhibitors that target FTO were reported to have potential for the treatment of BC by inhibiting cell proliferation and promoting apoptosis. However, the exact mechanism by which m6A modifications are regulated by FTO inhibitors remains unknown. m6A modifications in BC have only been preliminarily studied, and their mechanisms require further investigation.